The Role OF Human Resource managment Strategies In Enhancing Cognitive Skills. - الزبيدي غني دحام; محمود سناريا عبد الله (Journal of Economics and Administrative Sciences, 2016)
Abstract: In its theoretical farm, the research adobet the subject of human resource management strategies and the cognitive skills. It comes as result of the rapid development which considers it human resource. as main axis in organization , the research in includes ,connective analysis , between human resource management strategies and cognitive skills which is considers one of the new concept that should be studied widly so that the organization can be able recognize it as concept and type and its importance for people in the organization.The study method was descriptive and analytics , it identified collation of hypothesis which were by statist tools , mean, standard deviation ,correlation coefficient Group of (78)questionnaires from ministry of science and technology were interviewed as a simple for limited employees came to a results that the total of human resource management strategies contributed in effecting cognitive skills moreover , the study offered sum suggestions which could be useful for the ministry of science and technology